Sustainable Production of Biofuels from Microalgae (Chlorella vulgaris) Using Irradiation Microwave as Future Green Energy; a Review - Krisdayanti, Shendy; Fauziyyah, Hasna Amalia; Ubay, Isnina Noor; Erliana, Savira Rinda (Universitas Negeri Semarang, 2024)
Biodiesel is a solution to the problem of depleting fossil fuel sources in Indonesia. Biodiesel can be derived from vegetable and animal fats. On the other hand, microalgae cultivation areas are spread across 26 provinces in Indonesia with a production potential of 462,400 tonnes/year. Microalgae with lipid content ranging from 38% - 60% can be converted into crude biodiesel as much as 35%. Irradiation microwave is the simplest and most effective technology with a constructive method for extracting oil from animal and vegetable fats, and biomass, and can be scaled easily. Using irradiation microwave, oil will be extracted from microalgae using hexane: methanol solvent for 60 minutes with a microwave power of 600 watts. Microalgae extraction with the help of irradiation microwave can produce more lipids compared to conventional lipid extraction which is 31% and 26% higher. Microalgae that go through a treatment process using irradiation microwave is more efficient because the average cost is two-thirds less compared to conventional heating, its lower energy consumption, lower costs, a more effective heating process, can increase production, and have a big impact on increasing biofuel yields.